STRATEGI KREATIF KAMPANYE SOSIAL ORGANISASI BERBASIS KOMUNITAS â€œRUMAH CEMARAâ€ BANDUNGMELALUI MEDIA SOSIAL - R.A DITA SARASWATI (Serat Rupa: Journal of Design, 2016)
In 2014 social campaign and counseling for HIV and AIDS has been run by government or Health Ministry of the Republic of Indonesia, which aimed to make young people know how to prevent HIV/AIDS withother information related to myths and facts. Different with the government preventive campaign, an organization called Rumah Cemara in Bandung focusing to people that already infected by HIV/AIDS, especially teenager with former drug addicts background. Rumah Cemara is a communityâ€“based organization which aims to improve the quality of people living with HIV and Napza addict in Indonesia through peer approach support. Rumah Cemara is the largest network of people with HIV and Napza in West Java Province in Indonesia. With interview technique, documentation as well as literature studies of campaign and social media, the writer intend to analyze the role of social media and creative strategy campaign this organization runs for over 3 years, from 2013 to 2015. In their campaign strategy, they succesfully gain attention not only from the people living with HIV/drug addicts, but also the major society of Bandung about the discrimination problems towards the people living with HIV/AIDS.Â  This research aims to describe the creative strategy in socialmedia which popularly used by indonesian. This research also beneficial as a reference and reviews for social campaign for organization / other communities in Indonesia.Â Keywords: community; creative strategy; HIV/AIDS; social mediaÂ